Pengaruh Dukungan Sosial Terhadap Psychological Well-Being Pada Dewasa Madya - Idrus, Nahda Wafiah; Daud, Muh. (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Individuals who are in the middle adulthood phase will be faced with various unwanted circumstances and events. These conditions include physical deterioration, health problems, job loss, empty nest syndrome, and fear of death. Psychological well Being is a term used to describe a person's psychological health based on fulfilling the criteria of positive psychological function. This study aims to determine the effect of social support on psychological well being in middle adulthood. Respondents in this study were 203 middle adults in Makassar City who were obtained using a purposive sampling technique. The results of simple regression analysis showed that there was an effect of social support on psychological well being in middle adulthood with a significance value of 0.000, p <0.05. The R Square value in this study is 0.401 which indicates that the contribution of social support to psychological well being in middle adulthood is 40.1%. This indicates that the higher the social support obtained by middle adults, the higher the level of psychological well being of middle adults. This research can provide education for families and communities about the importance of the influence of social support on the level of psychological well-being of middle adults and can become study material for middle-aged individuals to be able to achieve high psychological well-being